Endoscopic 'Antireflux' Procedures: Not Yet Ready For Prime Time - Joseph Romagnuolo (Canadian Journal of Gastroenterology)
Gastroesophageal reflux disease affects a significant portion of the North American population on a weekly and daily basis. Options, especially for erosive disease, involve long-term proton pump inhibitors or surgical fundoplication. More recently, a number of endoscopic antireflux techniques have been assessed. These fall into three broad categories: the Stretta (radiofrequency); endoscopic suturing and plication devices; and injectable bulking agents. In the present summary, the literature on these endoscopic techniques is critically reviewed, highlighting the unimpressive efficacy, potential and real complications, and the relevant methodological limitations of the studies. Although they are promising, it is clear that these procedures are still in a preliminary study phase and not ready for 'prime time' clinical use.